Care delivery, patient experiences, and health outcomes among sexual and gender minority patients with cancer and survivors: A scoping review - Kent, Erin E.; Wheldon, Christopher W.; Smith, Ashley Wilder; Srinivasan, Shobha; Geiger, Ann M. (Cancer, 2019)
Sexual and gender minorities (SGMs) face a disproportionate burden of cancer, yet little is known about the experiences and specific needs of these underserved populations in cancer care delivery. The authors conducted a scoping review to characterize the literature on cancer care delivery, health outcomes, and health care experiences for patients with cancer and survivors identifying as SGM. In total, 1176 peer‐reviewed citations were identified after a systematic search of the PubMed/Medline, PsycInfo, Cumulative Index of Nursing and Allied Health Literature (CINAHL), and Web of Sciences databases without restriction on publication date. The details captured included study aims, design, population, cancer site, and main findings. Thirty‐seven studies published from 1998 to 2017 met the study criteria. Most studies were conducted in the post‐treatment survivorship phase of the continuum (n = 30), and breast cancer was the most common cancer site (n = 20). There were only 2 intervention studies. The studies reviewed were classified under the following areas of focus: 1) disclosure of sexual orientation and gender identity, 2) quality of care, 3) psychosocial impact of/ adjustment to cancer, 4) social support, 5) sexual functioning, and 6) health risks/health behavior. Very little research reported an assessment of gender minority status or included a focus on gender minorities (n = 7). This review revealed substantial research gaps given a lack of population‐based data and small sample sizes, likely related to the absence of systematic collection of sexual orientation and gender identity information in the cancer care context. Deficient research in this area likely perpetuates health disparities. Further research is needed to identify and remove the barriers to delivering high‐quality care to SGM individuals with cancer. Because sexual and gender minorities face a disproportionate burden of cancer, the authors conducted a scoping review of the experiences of sexual and gender minority patients with cancer in cancer care delivery. Findings to guide future research are presented from 37 studies on: 1) disclosure of sexual orientation and gender identity, 2) quality of care, 3) psychosocial impact of and adjustment to cancer, 4) social support, 5) sexual functioning, and 6) health risks and health behavior.